Informovaný souhlas - Pafko, P; Mach, J (Rozhledy v chirurgii, 2013)
Unless it is necessary to provide immediate assistance to a patient who, due to his state of health, is unable to give consent, every medical treatment must be performed with an voluntary consent from the patient. The patient must be informed, in advance, about the purpose and nature of the treatment, its consequences and risks. If the patient refuses the proposed treatment he must be notified about the possible harmful effects of this decision for his health (life) and the patient must sign a written refusal of the medical treatment - commonly known as revers. In case the patient refuses both the treatment and the signature, then the refusal must be signed by a witness. Informed consent may be oral; its written form is obligatorily dictated by law only in exceptional cases. Every health service provider is solely responsible for deciding which treatments will require written consents. The refusal form, revers, must always be written. The European courts have been emphasising that the most significant thing is the dialogue between the doctor and the patient, not the signed document. The patient must be informed by a relevant doctor about the treatment he is about to undergo not by a nurse or a doctor who will not be performing it. It is questionable whether it would not be better to substitute a written consent for an audio or audio-visual recording showing the interaction between the doctor and the patient, or his family. Anyone is allowed to express a future wish for situations when he will not be able to agree or disagree with the offered health services (that means previously expressed wishes - living will). The law will determine the formalities of such a document. Previously expressed wish should be respected unequivocally, although, its fulfillment must not lead to active cause of death. The rule is that human free will gives way to the protection of his life.
Keywords: Physician-Patient Relations; Informed Consent; Advance Directives; informovaný souhlas pacienta; lidé; Humans; Male; mužské pohlaví; vztahy mezi lékařem a pacientem; pacientova přání ohledně budoucí terapie